The Anterior Hyperfunction Syndrom - Fem Simulation - Cătălina Murariu Măgureanu; Elena Preoteasa (Romanian Society of Oral Rehabilitation, 2010)
Objectiv: Establishing a corelation of biomechanic behaviour with clinical observations, of the support area of masticatory presions, through out specific changes which characterise the anterior hyperfunction syndrom. Material and method: Starting with some oclusal considerations there are presented clinical observations concerning the anterior hyperfunction syndrom with predisposant factors, manifestation and consequenses. There are evaluated, using finite element method FEM, the oclusal presions, analizing the support area and their efects on oral structures, for oclusal forces of 100N. Results and conclusions: The biomechanic results with FEM are confirming the role of residual ridge in lateral area as zone of primary support and the important resorbtion in frontal ridge leading to flaby ridge, that caracterise the anterior hyperfunction syndrom. The biomechanic results by FEM confirmes the lateral ridge as primary support, and also the accelerated resorbtion in frontal crest, that appears in anterior hyperfunction syndrom.